Analisis Penerapan Manajemen Strategi Budidaya Burung Kenari (Studi Kasus Pada Kenari Mcp Kota Mataram) - Firmansyah, Harry; Animah; Isnawati (Fakultas Ekonomi dan Bisnis Unram, 2024)
The purpose of this study was to determine and analyze how the implementation of canary cultivation strategy management at MCP Walnut Jl.Swakarya Raya Gg 2 No. 8 Pagesangan Mataram City. This research design is field research (Field Research). While the research approach is descriptive qualitative. Besides being researched with a qualitative descriptive approach, this research also uses the SWOT analysis method (Strenght, Weakness, Opportunity, Treath). SWOT analysis is used by researchers to analyze external factors, namely opportunities and threats, but also internal factors, namely strengths and weaknesses. Data collection was carried out using interview and documentation techniques. The data findings are described descriptively. The results of this study can be seen that this study has five strengths (Strenght), has three weaknesses (Weakness), has three opportunities (Opportunity), and has three threats (Threats). Based on the IFAS and EFAS Matrices, the strategies applied by MCP Kenari are SO, ST, WO, and WT strategies. Because this strategy signifies the state of canary cultivation that is strong and able to continue to grow by taking opportunities or opportunities that exist to achieve maximum turnover in increasing income.